Stress coping strategies of medical students in wartime conditions - Огоренко, Вікторія; Шустерман, Тамара; Ніколенко, Алла; Кокашинський, Віктор (Psychosomatic Medicine and General Practice, 2023)
This text is the thesis of the conference "Psychosomatic Medicine: science and practice". Which took place on April 21-23, 2023 in the city of Kyiv on the Mediamed portal. The following is devoted to stress coping strategies of medical students in wartime conditions.